Strong light-matter coupling for reduced photon energy losses in organic photovoltaics - Vasileios C. Nikolis (Nature Portfolio, 2019)
Strong light-matter coupling can tune exciton properties but its effect in photovoltaics remains unexplored. Here Nikolis et al. show that the photon energy loss from optical gap to open-circuit voltage can be reduced to unprecedented values by embedding organic solar cells in optical microcavities.